Investigating the role of phosphorylated regulatory light chains during heart failure progression - Markandran, Kasturi (Nanyang Technological University, 2022)
It is established that enhanced Regulatory Light Chain (RLC) phosphorylation in muscle improves its contractility. Incidentally, it is observed that the levels are enhanced during the compensatory phase of heart failure (HF) and reduced in the decompensatory phase, where muscle contractility is compromised. However, it is not known if the changes in RLC phosphorylation status drives the cardiac functional changes during HF progression or if HF progression drives the changes in RLC phosphorylation status. Thus, the 28-day longitudinal profiles of maximal isometric force and RLC phosphorylation were superimposed, and the results suggest that RLC phosphorylation changes transiently to sustain contractility in the compensatory phase. The potential of RLC in reversing contractile disease is explored by enhancing RLC phosphorylation levels, via in vitro exchange methods, in muscle fibre in the decompensatory phase. The enhancement improved contractility substantiating the use of phosphorylated RLCs as small molecule treatment for HF.